Pengaruh Kepemilikan Manajerial Terhadap Profitabilitas Dan Kinerja Saham (Studi Kasus Pada Perusahaan Manufaktur Sektor Barang Konsumsi yang Terdaftar di BEI Periode 2016-2018) - Kuswatun Hasanah; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT The purpose of this study is to find out how the effect of managerial ownership which is proxied by managerial ownership on the profitability and performance of this research stock is a type of quantitative research. The population take in this study is the consumer goods manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during the 2016-1018 period. The sample was selected using purposive sampling with data from 39 companies but from 39 companies there were 14 companies whose financial data were incomplete which did not match the variables in the researchers, only 21 companies were selected as samples. The results of showed that good corporate governance has a significant negative effect on profitability. managerial ownership has a significant positive effect on stock performance. Keywords: managerial ownership, profitability, and stock performance